Impact of In-House Bolus Thickness on The Percentage of Surface Dose for 10 and 12 MeV Electron Beams - Sigma Nur Rismawati; Johan Andoyo Effendi Noor; Yuyun Yueniwati; Fatimah Kunti Hentihu; Margaretha Berek; Ayu Hardianti Pratiwi; Karimah Karimah (Jurnal Penelitian Pendidikan IPA, 2022)
The surface dose on electron irradiation which is received by the skin does not reach 100%, so a bolus is needed as a compensator material in order to reach or approach 100%. This study aims to create, test, and describe the effect of different thicknesses of boluses that are made of 3D printed TPU, silicone sealant and resin on equivalence with tissue and the percentage of surface dose produced. A bolus with a size of 15x15 cm2 and with variations in thickness of 0.3 cm, 0.5 cm, and 1 cm was imaged by a CT-Scan to analyze the CT-Number value and relative electron density using imageJ software. After that, the bolus was irradiated by a Linac with an energy of 10 MeV and 12 MeV to measure the surface dose using an advances marcus detector. The result of this study showed that 3D printed TPU, silicone sealant and resin are similar to some soft tissues. Silicone sealant has the highest flexibility of the two boluses. In addition, silicone sealant also produces the highest increase in the percentage of surface dose in phantom.